2020
DOI: 10.1002/app.49519
|View full text |Cite
|
Sign up to set email alerts
|

Study of microwave‐template initiated copolymerization peculiarity and evaluation on the coal floc distinctive behavior and flocculation performance

Abstract: Cationic polyacrylamide (CPAM) contains a large number of acylamino and positively charged methyl ammonium chloride groups. It has the advantages of good water solubility, strong adsorption bridging ability, enhanced charge neutralization and destabilization performance, excellent flocculation effect, and wide application. Therefore, CPAM can be used in the treatment of coal washing wastewater, and the research and development of a new flocculant with high efficiency is a hot topic in this field. Template copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The chemical shifts of secondary carbon atoms (C j ), tertiary carbon atoms (C k ) and quaternary carbon atoms (C l ) on the polymer backbone were observed at 35-38 ppm, 42-43 ppm and 44-45 ppm, respectively. These results demonstrated that AAPs were successfully synthesized [26]. Among the cationic monomers used for polymerization, DMC, DAC, and DMAEMA are acryloxy-alkyl cationic monomers with ester group in the side chain.…”
Section: Structural Characterization Of Aapsmentioning
confidence: 74%
“…The chemical shifts of secondary carbon atoms (C j ), tertiary carbon atoms (C k ) and quaternary carbon atoms (C l ) on the polymer backbone were observed at 35-38 ppm, 42-43 ppm and 44-45 ppm, respectively. These results demonstrated that AAPs were successfully synthesized [26]. Among the cationic monomers used for polymerization, DMC, DAC, and DMAEMA are acryloxy-alkyl cationic monomers with ester group in the side chain.…”
Section: Structural Characterization Of Aapsmentioning
confidence: 74%